Systematic and locomotor diversification of the Adapis group (Primates, Adapiformes) in the late Eocene of the Quercy (Southwest France), revealed by humeral remains. Issue 126 (January 2019) - Marigó, Judit; Verrière, Nicole; Godinot, Marc
Abstract: Twenty humeral specimens from the old and new Quercy collections attributed to the fossil primates Adapis and Palaeolemur are described and analysed together. We provide a qualitative and quantitative analysis of the different humeri, revealing that high variability is present within the " Adapis group" sample. Six different morphotypes are identified, confirming that what has often been called " Adapis parisiensis " is a mix of different species that present different locomotor adaptations. Such a relatively high level of locomotor diversity is unique in the Paleogene primate fossil record. The humeral proportions of Adapis overlap with different groups of extant strepsirrhines and platyrrhines depending on the specimen, so the popular view of Adapis as a loris-like slow climbing primate does not apply to the whole sample presented here. Moreover, different humeral features traditionally associated with " Adapis parisiensis ", such as the absence of a zona conoidea and a reduced brachioradialis flange, are variable depending on the sample studied. In addition, results of our analyses show that adapine and omomyid humeral morphology overlap extensively, leading us to question the accuracy of taxonomic attributions based on morphology of isolated humeri at localities where omomyids and adapines of similar size coexist. Finally, assuming our different morphotypes represent different species within two genera, we propose a phylogenetic hypothesis relating these morphotypes, which inhabited a small geographic area.